HUBUNGAN PENGETAHUAN DENGAN TINGKAT KECEMASAN REMAJA PUTERI TENTANG DISMENORHEA DI SMPN 09 BATHIN SOLAPAN - Diana, Nana; Agustina, Santi (Ensiklopedia of Journal, 2024)
Dysmenorhea (pain during menstruation) is one of the menstrual problems that are often experienced in women, especially in adolescents. In the world, this incidence rate occurs almost 50% of women have experienced menstrual pain during adolescence. This will sometimes interfere with the activities of the teenager. Usually this disorder reaches its peak at the age of 17-25 years. This study aims to identify the relationship between knowledge and the level of anxiety of adolescent girls about dysmenorrhea at SMPN 09 Bathin Solapan. This study design is correlation analytical with a cross sectional approach with a sample size of 219 people with a stratified random sampling method. This study was conducted from January 2023 to April 2023. The instruments in this study were questionnaires that included demographic data, knowledge questionnaires about dysmenorrhea, and questionnaires about anxiety levels. The results showed that the majority of adolescent girls were well informed as many as 167 people (76.3%) and experienced mild anxiety as many as 150 respondents (68.5%) about dysmenorrhea. After the chi-square test, it was concluded that there was a significant relationship between knowledge and the level of anxiety of adolescent girls about dysmenorrhea because the p value < 0.05 or (0.002 < 0.05). From this research it is expected that adolescents will further increase knowledge about dysmenorhea.Keywords: Knowledge, anxiety level, dysmenorhea.